2016
DOI: 10.1039/c6ob01214k
|View full text |Cite
|
Sign up to set email alerts
|

The past, present, and future of the Yang reaction

Abstract: Photoexcited ketones have diradical characteristics and are functionally similar to high-spin metal–oxo species that are frequently used to catalyze C–H oxidation. First discovered by Yang in 1958, photoexcited ketones can abstract a hydrogen atom from hydrocarbons inter- or intramolecularly. Coupling with atom-transfer, group-transfer, or radical addition, the Yang reaction can be used to achieve various types of C–H functionalization. We provide in this article an overview of triplet ketone-mediated or catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 86 publications
0
43
0
Order By: Relevance
“…In the Norrish type II the exited ketone is converted to its 1,4‐biradical through an 1,5‐intramolecular hydrogen atom transfer (1,5‐HAT) (Scheme b). This intermediate can undergo many transformations, the elimination and the Yang cyclization being the most common . These two previously described transformations are exclusively for aliphatic ketones, while photoexcited bis‐arylketones, alkyl‐arylketones and 1,2‐diketones are also able to participate on intermolecular hydrogen abstractions, being normally reduced to the respective ketone or dimerized (pinacol coupling product) in the end of the reaction course (Scheme c) .…”
Section: Photochemistry Of Carbonyl Compounds: Fundamental Aspects Anmentioning
confidence: 99%
“…In the Norrish type II the exited ketone is converted to its 1,4‐biradical through an 1,5‐intramolecular hydrogen atom transfer (1,5‐HAT) (Scheme b). This intermediate can undergo many transformations, the elimination and the Yang cyclization being the most common . These two previously described transformations are exclusively for aliphatic ketones, while photoexcited bis‐arylketones, alkyl‐arylketones and 1,2‐diketones are also able to participate on intermolecular hydrogen abstractions, being normally reduced to the respective ketone or dimerized (pinacol coupling product) in the end of the reaction course (Scheme c) .…”
Section: Photochemistry Of Carbonyl Compounds: Fundamental Aspects Anmentioning
confidence: 99%
“…On the basis of the well-established reactivity of excited state diaryl ketone diradicals, which form ketyl radicals upon hydrogen atom abstraction (HAT) from both activated and unactivated C(sp 3 )–H bonds, 47 we envisioned a tricatalytic mechanism for net C–H arylation (Scheme 20). Early studies employing THF as H atom donor and solvent with one equivalent of benzophenone under standard coupling conditions afforded the desired product, albeit in moderate conversion.…”
Section: Photoredox/nickel Dual Catalysismentioning
confidence: 99%
“…It has been documented that triplet carbonyls can abstract hydrogen atoms, especially those adjacent to heteroatoms (such as the O atom in ethers and alcohols), to produce the hydroxyalkyl radical. 44,45 Inspired by this and following our continued interest in photochemistry as a greener alternative to traditional transition-metal-catalyzed chemistry, [46][47][48][49][50][51][52][53][54] we anticipated that simply adding ketones into the reaction system would increase the generation rate of hydroxymethyl radical 15 (,CH 2 OH) because, under light irradiation, triplet ketone would be able to abstract the a-H of MeOH efficiently, 45 eventually leading to the efficient formation of direct-methylation product (16). Different from Jin and MacMillan's system 34 involving iridium photo-redox catalyst and odorous thiol organocatalyst, both of which are either expensive or not friendly to handle, we expected this system to avoid external catalysts and be driven solely by the solvent's intrinsic properties (Scheme 2B).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there has been a demand to synthesize tri-deuteromethylated heterocycles. 20,56 It was found that with this protocol, 2-methylquinoline could be tri-deuteromethylated with 76% yield (45), although other positions were also partially deuterated. Delightfully, purine-type substrate, as a key structural motif in many top-selling drugs, can also be methylated under the standard conditions (46).…”
Section: Scope Of the Investigationmentioning
confidence: 96%